Studies in law, politics, and society. Vol. 61 - Sarat, Austin (Bingley, U.K. : Emerald, 2013)
This volume of Studies in law, politics and society brings together an international spread of legal scholars, presenting a varied collection of chapters. Chapters include: child abduction during the military dictatorship in Argentina; a novel approach to empirical research on legal framing from the University of California, Berkeley; the role of silence in law and film from Israel; a chapter from Sweden on the use of video in the court of appeal; and finally two chapters on the supreme court in the USA, one looking at influences through social capital on supreme court decision makers and the second looking at the self-perception and public perception of the supreme court.
Redefining the abduction of children : legal truth in post-dictatorial Argentine courts of law/ Natacha V. Osenda -- Legal framing / Gwendolyn Leachman -- The silent defendant : some thoughts on law and film / Yofi Tirosh -- A modern trial : a study of the use of video-recorded testimonies in the swedish Court of appeal / Leif Dahlberg -- "Its the network" : the federalist society as a supplier of intellectual capital for the supreme court / Amanda Hollis-Brusky -- The supreme court : an autobiography / Keith J. Bybee, Angela G. Narasimhan.
Print version record
Keywords: Social Science -- Anthropology -- Cultural; Cultural studies; Sociological jurisprudence; Political sociology